RELASI TOKOH DALAM NOVEL SASTRA INDONESIA SEBUAH PENDEKATAN MULTIINTERDISIPLINER - Rokhyanto (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2023)
This Indonesian Literary Novel contains various kinds of events, just like human events, even though living in the world is both mere fiction and reality. Every good literary work always carries ethical and moral messages, so good literature always voices ethical and moral appeals and is full of trust. The problem in this paper, namely: the relationship between characters in Indonesian literary novels through a multi-interdisciplinary approach. the problems that exist in the relations between characters in Indonesian literary novels can be unraveled through a detailed description of the multidisciplinary nature of Indonesian literary novels. The purpose of this paper is to examine in detail: relations between figures through a multidisciplinary approach; existing problems and detailed descriptions according to the two interdisciplinarities in Indonesian literary novels through a multiinterdisciplinary approach. The method in this paper uses a qualitative approach, the research data is in the form of words, phrases, sentences, in the dialogues of the characters in Indonesian literary novels. The instrument is a data screening guide containing the presented data columns. Collection techniques in the form of text analysis and data collection procedures. It is hoped that the results of this study can serve as an additional basis for reference concepts for researchers who are interested in further exploring research on literature, especially multi-interdisciplinary disciplines. This article describes the results of the characters who care for the poor, and the friendship of two girls who are kind to each other, but one is poor and the other is rich.